Investigation of Acceptance of Illness and Religious Coping in Patients with Familial Mediterranean Fever in Turkey - Şentürk, Sibel (Journal of religion and health, 2022)
This study aimed to determine the Acceptance of Illness and use of religious coping in patients with Familial Mediterranean Fever (FMF). This descriptive and cross-sectional study was conducted with 209 FMF patients, who came to be examined in the Rheumatology outpatient clinic of a Training and Research Hospital in Turkey between June and October 2020. Data were obtained using a Patient Information Form, the Acceptance of Illness Scale, and the Religious Coping Styles Scale. The patients' mean Acceptance of Illness score was 21.14 ± 8.44 (moderate level), their mean positive religious coping score was 20.46 ± 5.97, and their mean negative religious coping score was 10.63 ± 5.01. There was a weak, negative correlation between the patients' Acceptance of Illness and their negative religious coping. Nurses should help patients to develop their Religious Coping Styles by taking into consideration their beliefs, values, cultural, and social backgrounds.